2022
DOI: 10.3390/ijerph191710808
|View full text |Cite
|
Sign up to set email alerts
|

The Status of Occupational Stress and Its Influence on the Health of Medical Staff in Lanzhou, China

Abstract: This study aimed to understand the status quo of occupational stress and its impact on the health of medical staff and provide a theoretical basis for relieving occupational stress and improving the health status of medical staff. The occupational stress and health status of medical staff in 14 hospitals in Lanzhou were studied using a general questionnaire, Effort–Reward Imbalance questionnaire, and Self-Rated Health Measurement Scale. A total of 2169 participants were included in the analysis, and 59.4% of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…Community frontline medical workers with 20–29 years of service were more likely to suffer psychological problems (OR = 0.137; 95% CI = 0.029–0.653). This result is similar to previous studies ( 50 , 51 ), which may be related to this group being facing the position of supporting the elderly and taking care of children at the same time. Therefore, community managers should pay attention to the mental health of frontline medical workers, especially frontline medical workers with high education, no fixed contract and more than 10 years of work, giving care, reasonably arranging work, and promoting their mental health.…”
Section: Discussionsupporting
confidence: 92%
“…Community frontline medical workers with 20–29 years of service were more likely to suffer psychological problems (OR = 0.137; 95% CI = 0.029–0.653). This result is similar to previous studies ( 50 , 51 ), which may be related to this group being facing the position of supporting the elderly and taking care of children at the same time. Therefore, community managers should pay attention to the mental health of frontline medical workers, especially frontline medical workers with high education, no fixed contract and more than 10 years of work, giving care, reasonably arranging work, and promoting their mental health.…”
Section: Discussionsupporting
confidence: 92%
“…More so, with the development of society and continuous advancement in science and technology, the work requirements for professional people are constantly improving, and the detection rate of occupational stress also increases. (16) A recent survey carried out by the Association of University Teachers found that 69 % of academic and related staff found their job to be stressful and 50 % reported psychological distress. (17) The results of the present study revealed that most of the lecturers sometimes feel emotionally drained from their work.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, elevated levels of stress have been found to diminish the e ciency of employees and heighten the likelihood of occupational harm [26], [27]. It would be feasible to determine whether low-or high-income jobs are more at risk for occupational mental health [28].…”
Section: Discussionmentioning
confidence: 99%